The Philosophy of Mathematics Education - Ernest, Paul; Skovsmose, Ole; van Bendegem, Jean Paul; Bicudo, Maria; Miarka, Roger; Kvasz, Ladislav; Moeller, Regina (ICME-13 Topical Surveys, 2016)
VII, 26 p.